Association of C-reactive Protein and Partial Mayo Score With Response to Tofacitinib Induction Therapy: Results From the Ulcerative Colitis Clinical Program - Dubinsky, Marla C.; Magro, Fernando; Steinwurz, Flavio; Hudesman, David P.; Kinnucan, Jami A.; Ungaro, Ryan C.; Neurath, Markus; Kulisek, Nicole; Paulissen, Jerome; Su, Chinyu; De Leon, Dario Ponce; Regueiro, Miguel (Inflammatory Bowel Diseases, 2022)
Lay Summary Early decreases in partial Mayo score and C-reactive protein were found to be associated with achieving efficacy outcomes following tofacitinib 10 mg twice daily induction therapy in the ulcerative colitis clinical program.
CRIS-Team WoS Importer:2022-04-29